The Invention of «Humanity» in Twentieth century European Historiography: On the Treatment of Prisoners of War in the Hellenistic World - Moreno Leoni, Álvaro Matías (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
My aim in this article is to study the historiographical invention between 1920 and 1970 of the idea of a move towards humanising Hellenistic warfare, specifically in relation to the treatment given to prisoners of war during this historical period. I shall seek to link this historiographical construction with the contemporary context of the historians who wrote in the interwar period, and with the survival of a Eurocentric view that established a special continuity between the historical experiences of ancient Greece and modern Europe. Through an examination of other warfare practices in the broader cultural context of the ancient Eastern Mediterranean, I shall conclude by calling into question the very idea of Hellenistic Greek exceptionalism in attempting to moderate and regulate violence in warfare.